A Qualitative Study to Explore the Supply Chain Management in the Indonesia Pepper Industry: Case Study of Black and White Pepper - Kusuma, Fikar Ramadhan (2009)
In today’s business, supply chain management is considered as the key business objective which creates they way managers perceive on the company’s supply chain. Application on supply chain management has to bring added value and business benefit for the company, such as increase process efficiency, customers’ satisfaction, responsiveness, eliminate waste, lower inventory that meets demand, and reduce the need of working capital. Hence, companies can distinguish itself within the virtue of their objectives and able to compete with other value streams. This study aims to assess the supply chain management phenomenon by approaching the supply chain structure, supply chain challenges, and improvement of the supply chain. Questions on the way companies articulate the supply chain management, application on the supply chain management, and the implications towards the way supply chain is conducted, has revealed different arguments between the related supply chain management theories and the actual circumstances. Based on these objectives, a qualitative-based research methodoly is employed using six organizations related with the Indonesia pepper industry as the case study. Results indicate that companies involved in the Indonesia pepper supply chain are aiming to conduct an effective supply chain management. Nevertheless, companies have a low awareness to establish a clear vision towards conducting supply chain management. Therefore, there is limited ability for the supply chain members especially the focal companies to create added value. Based on the findings, this research provides implication to the Indonesian pepper businesses and related pepper organizations.